A case study on teachers' beliefs and classroom practices of communicative language teaching at three Vietnamese high schools in Tra On district : - Lê, Hồng Kha (Can Tho University, 2008)
This paper reports the results of my study on teachers' beliefs and classroom practices of communicative language teaching, and the impacts of teachers' implementation of communicative language teaching on students' language anxiety and oral communicative competence at three different high schools in Tra On district.